Analisis Kualitas Layanan dan Kepuasan Pengunjung Perpustakaan Kampus A Universitas Nahdlatul Ulama Surabaya (Unusa) - Karya, Denis Fidita (UNUSA Press, 2016)
This research conducted a survey respondents visitors to 100 library campus aUnusa. The purpose of this research is to assess the level of the quality of services andsatisfaction visitors library campus a Unusa, so that it can be known how big level thequality of services and satisfaction visitors library. Research methodology it uses researchquantitative so that can be described clearly of the level of the quality of services andsatisfaction visitors library campus a Unusa. This research uses the importance performanceanalysis (ipa) used to know position strength and weakness of the indicators used.The result of research is obtainable 19 an indicator of the measurement of the quality ofservices library. In addition, this research results from for variables reliability and assurancehaving the same as it lies in quadrant two, while the rest those are variable tangible,responsiveness and empathy located at quadrant three.